THE EFFECT OF THE PROBLEM BASED LEARNING MODEL USED BY KOBELKA CONCRETE MEDIA AND THE IMPLEMENTATION OF CLASS MANAGEMENT ON THE NUMERATION SKILLS OF GRADE III STUDENTS - Khara Kharizesthai Princess Nusantoro; Herry Sanoto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study was motivated by the low multiplication numeracy skills of elementary school students due to learning practices that remain conventional and the minimal use of concrete instructional media. Based on theoretical studies, the Problem Based Learning model, concrete manipulative media, and effective classroom management can improve students’ conceptual understanding and learning engagement. This study aimed to determine the effect of implementing the Problem Based Learning model assisted by KOBELKA media and classroom management on students’ multiplication numeracy skills. This research employed a quantitative experimental approach with a quasi-experimental design in the form of a Non-Equivalent Control Group Design. The study was conducted at SD Negeri Bringin 01 (experimental class) and SD Negeri Bringin 02 (control class). Data collection techniques included tests (pretest-posttest), observation, and documentation. The research instrument consisted of multiple-choice questions that had been tested for validity and reliability. Data analysis included descriptive tests, normality tests, homogeneity tests, N-Gain analysis, and hypothesis testing using the Wilcoxon test, paired sample t-test, and Mann-Whitney U Test. The results showed a significant difference between the experimental and control classes (sig. < 0.05), with a higher improvement in numeracy skills in the experimental class. Therefore, the implementation of the Problem Based Learning model assisted by KOBELKA media and classroom management had a significant effect on improving students’ multiplication numeracy skills.